Exploration the concept of thayyiban halal food in the primary school environment: a study of students' halal literacy - Sumiati, Iis; Windayani, Neneng; Nuryantini, Ade Yeti (Journal of Halal Product and Research (JHPR), 2024)
Food and drink are basic human needs that must be met every day. In Islam, the food and drink consumed must not only be halal (permissible), but also must be thayyib (good and beneficial). The introduction of the concept of thayyiban halal food has become an important element that has penetrated people's mindset. In an educational context, an understanding of this concept is very important to instill from an early age. This research aims to investigate the halal literacy profile of students in concept of halal food and thayyib in primary schools. A survey method with field observation was used to collect data from 40 students in grades 4, 5 and 6 at Beribu Foundation Elementary School. Data was collected through halal literacy questionnaires and interviews to gain in-depth understanding. Data analysis uses a descriptive approach to provide a clear picture of students' understanding of the concept. The research results show that there are variations in students' understanding, where most are close to correct understanding while others require deeper understanding. This research makes an important contribution in understanding the halal literacy profile of students at the elementary school level and can be a basis for developing better education in the concept of halal food and thayyib in the future.